A Comparative Study of Two Small and Remote Urban Communities: Implications for Social Policy and Practice (A Tale of Two Towns) - Rivlin, Judith Rochelle Lardner (Auckland University of Technology, 2010)
Defined as resource communities and independent urban centres, Raetihi and Ohakune are two small and remote towns on the North Island of New Zealand’s Central Plateau. They have similar sized populations and are set approximately 12 kilometres apart, yet present as totally different communities. Raetihi is a declining farming service centre, with a majority Maori population and the statistics of a town facing relative disadvantage. In contrast, Ohakune is a bustling tourist town of predominantly Europeans, with a statistical profile that indicates relative prosperity. However, this is only a part of the picture. This research presents a more complete picture, including a historical review which details the stories of these towns, set within the context of the wider changes occurring throughout the country. The model of resource community cycles (Taylor and Fitzgerald, 1988) is used to provide an overview of the development of these towns, covering the eras of sawmilling, railways, farming, market gardening and more recently, tourism. Theories of civil society and social capital provide a framework for analysis of the internal dynamics of the communities. This analysis contributes to possible explanations for the existing disparities, as well as to strategies that address them. Indicated through this analysis, was a shortage of stocks of bridging social capital, both within and between the towns. These are the bridges between different social networks that enable communities to “get ahead” (Kozel and Parker 1998; Barr 1998; Narayan 1999). Strategies suggested to develop bridging social capital include: the development of networks of interest, such as a youth network; and activities that promote common interests, such as the arts, sports, shared celebrations and the importance of families. Also highlighted was a need for capacity building, particularly within the Raetihi community. This is in order to foster more effective processes for public engagement required for the development of strong bridging social capital, as well as linking social capital, i.e. the vertical links referring to the dimensions of social class and group power dynamics. A comparative approach has highlighted cultural differences between Maori and European based understandings of the concepts of family, community, voluntary work and associational life, which has implications on theories of civil society. Cultural differences in values were also seen to be reflected by attitudes towards the mountain and rivers in the area. Europeans saw them as economic assets, whereas the Maori view was that they held a spiritual significance as respected ancestors. The dominance of the European view was promoted through the public sphere with an emphasis on tourism and economic development, and the exclusion of community development, representing a hegemony of values. There was a need identified for more inclusive processes for community decision making and a mandate that addresses the pervasive inequalities that exist. The communities' experiences of government agency initiatives highlighted a resulting shortage of sustainable community development outcomes. This was seen to be mainly due to the agencies being centrally located and controlled, with limited interagency communication. There was also a tendency for agencies to operate from a model of service provision to a passive community, rather than the dialogical partnership relationship (Ife 1997:133) necessary for effective and equitable community development. With a limited mandate held by local government for such community involvement, a small and stretched voluntary sector, the inevitable result has been the maintenance of the status quo. Efforts need to be made to support a viable future for these independent urban centres, as they face predictions of a declining and aging population and increasing inequality. Traditionally, efforts that promote equitable development through the redistribution of resources and power are built on arguments of social justice. However, a contribution of theories of social capital and civil society is to highlight the need for equality within and between communities, to ensure the capacity, strength and efficiency of the social networks necessary for strong, sustainable, economic development. To maximise a community's economic performance, equitable community development must first be addressed.
Keywords: Community studies New Zealand; Raetihi; Ohakune; Rural New Zealand; Social capital; Civil society